Mental visualization exercises and their impact on developing the accuracy of straight punches among young boxing players - Majeed, Ali; QusaY, Mohammed (Journal of Physical Education, 2022)
The research aimed to identify the impact of mental training in developing the accuracy of straight punches among young boxing players. The research problem lies in the fact that some of the trainers do not have information about the importance and effectiveness of mental training, as well as their curricula and training units lack mental visualization exercises. The researchers used the experimental approach by designing one group with a pre and post-test. The subject was (10) young boxers at the ages of (14-15) years. the researchers concluded that mental imagery leads to the fixation of the skill through mental retrieval.